Assessment of the feed additive consisting of endo‐1, 4‐β‐xylanase produced by Trichoderma reesei CBS 114044 (ECONASE® XT) for piglets (weaned), chickens reared for laying, chickens for fattening, turkeys for fattening and turkeys reared for breeding for the renewal of its authorisation (Roal Oy). (23rd February 2021) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the ECONASE ® XT, an enzyme based on endo‐1, 4‐β‐xylanase produced by a genetically modified strain of Trichoderma reesei CBS 114044. The additive is currently authorised for use in chickens for fattening, chickens reared for laying, laying hens, turkeys for fattening, turkeys reared for breeding, minor poultry species, piglets (weaned) and pigs for fattening. ECONASE ® XT is currently authorised in two forms, a solid and a liquid form with activities of 4, 000, 000 and 400, 000 BXU/g, respectively. In a previous opinion, the FEEDAP Panel could not exclude the potential presence of recombinant DNA derived from the production organism in recent batches of the additive. The applicant has submitted data to support the absence of recombinant DNA derived from the production organism in recent product batches. The FEEDAP Panel confirms that the data provided support the absence of recombinant DNA of Trichoderma reesei CBS 114044 in the additive and thus, no safety concern was identified.